The Palgrave Handbook of the Sociology of Work in Europe - Stewart, Paul.; Durand, Jean-Pierre.; Richea, Maria-Magdalena.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the key conceptual features of the development of the Sociology of Work (SoW) in Europe since 1945, using eleven country case studies. An original contribution to our understanding of the trajectory of the SoW, the chapters map the current state of the theoretical background of the sub-discipline's development to broader socio-political and economic changes, traced across a heterogeneous set of national contexts. Different definitions of the SoW in each country often reflect variations in the focus of analysis, and these chapters link the subject definition and focus to other social science disciplines, the state, as well as social class interests and ideologies. The book contends that the ways in which the sub-discipline makes sense of changes in work is itself a response to the type of society in which the sub-discipline is practiced, whether in the post-war social democratic West, the Soviet East, or today's societies, dominated by variant forms of neo-liberalism. It will be of use to scholars and students interested in the transnational history of the discipline of sociology, with a specific focus on the nexus between the sociology of labour, ideology, economics and politics.
Chapter 1. Towards a Sociology of the Sociology of Work in the UK since 1945: The Myth of the Golden Age; Carol Stephenson, Paul Stewart, David Wray -- Chapter 2. The Sociology of Work in France, Guillaume Tiffon, Jean-Pierre Durand. - Chapter 3. Sociology of Work in Germany; Holm-Detlev Köhler -- Chapter 4. Labour Sociology in Italy: Resisting Erosion Through Transformation and Dynamism; Valeria Pulignano -- Chapter 5. The Politics of Sociology and the Challenges of Transitions, Formalisation and Fragmentation: The Study of Work and Employment in Spain; Miguel Martínez Lucio, Carlos J. Fernández Rodríguez. - Chapter 6. Swedish Sociology of Work; Bengt Furåker -- Chapter 7. The Sociology of Work in Finland; Markku Sippola, Tuomo Alasoini -- Chapter 8. Sociology of Work in Poland; Adam Mrozowicki. - Chapter 9. Sociology of Work in Hungary; Violetta Zentai -- Chapter 10. Sociology of Work in Bulgaria; Vassil Kirov. - Chapter 11. Sociological Approaches to Work in Romania Since 1945; Norbert Petrovici, Florin Faje. - Conclusion; the Editors and the Authors. .
Keywords: Industrial sociology; Labor; History; Personnel management; Sociology of Work; Labor History; Human Resource Management